HARNESSING THE NEUROPROTECTIVE POTENTIAL OF PUERARIA TUBEROSA TUBER THROUGH OXIDATIVE STRESS MODULATION AND ANTICONVULSANT ACTIVITY - TRUPTI DURGAWALE; JYOTIRAM SAWALE; PRATIK DURGAWALE; SUHAS PADMANE (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The study aimed to assess the phytochemical profile, anticonvulsant activity, and antioxidant potential of ethanol, butanol, and aqueous Pueraria tuberosa tuber extracts. Methods: Preliminary phytochemical screening was performed using standard chemical tests. In male Swiss albino mice, anticonvulsant activity was assessed using two models: seizures caused by pentylenetetrazole (PTZ) and maximal electroshock seizures (MES). Male Wistar rats were administered the extracts (100 mg/kg, p.o.) for 14 days to evaluate their antioxidant levels. Catalase, superoxide dismutase (SOD), glutathione (GSH), and malondialdehyde (MDA) levels were assessed in brain tissue homogenates. One-way analysis of variance and Dunnett’s test were used for statistical analysis. Results: Phytochemical analysis confirmed the presence of steroids, saponins, flavonoids, alkaloids, and tannins in all extracts. In the MES model, the ethanol and butanol extracts significantly reduced extensor phase duration (6.54±1 s and 6.32±0.57 s, p<0.001, respectively) compared to the control, closely approaching the standard drug phenytoin (4.33±0.57 s, p<0.001). In the PTZ model, the butanol extract showed the highest anticonvulsant activity, with a delayed onset of clonus (138.33±0.57 s, p<0.001), prolonged clonus duration (304.23±1.52 s, p<0.001), and 83.3% protection. The ethanol and aqueous extracts provided 66.6% and 33.3% protection, respectively. According to antioxidant analysis, the butanol and ethanol extracts had substantial antioxidant effects, as evidenced by the considerable increases in catalase, SOD, and GSH levels and the decrease in MDA concentrations. Conclusion: The extracts of P. tuberosa, particularly the butanol and ethanol fractions, exhibited strong anticonvulsant and antioxidant activities, indicating their therapeutic potential in the management of seizures and oxidative stress-associated neurological disorders.